An Evaluation of Implementation Nosocomial Infection Prevention and Control Program in The Space Covid-19 Isolation at Hospital Royal Prima Medan - Tommy Adhi Wijaya; Ermi Girsang; Sri Lestari Ramadhani Nasution (Budapest International Research and Critics University, 2022)
An Infectious diseases are still one of the health problems in the world, including in Indonesia. According to the World Health Organization (WHO) in 2013, the percentage of nosocomial infections in hospitals worldwide reached 9% (variation 3 – 21%) or more than 1.4 million hospitalized patients worldwide had nosocomial infections. At the end of 2019, there was an outbreak of a virus called Corona Virus Disease / COVID-19 in Wuhan City, China. Efforts to minimize the risk of infection in Royal Prima Hospital and other health facilities need to be implemented in infection prevention and control (PPI). Researchers are interested in evaluating how to implement a nosocomial infection prevention and control program in the COVID-19 isolation room at Royal Prima Hospital Medan. This research used is qualitative research with a descriptive approach with the method of determining the informants using purposive selection. The research was carried out in the Covid-19 Isolation Room of Royal Prima Hospital Medan. The sources of data or sources of information in the study were parties who were considered competent in providing internal information at the Royal Prima Medan Hospital related to nosocomial infections as many as 7 people consisting of the head of the Covid-19 isolation room at the RSU Royal Prima, PPI Team (Infection Prevention and Control in Hospitals) Royal Prima General Hospital, Five nurses on duty to nurse patients in the Covid-19 isolation room at Royal Prima Hospital. The results showed that the implementation of the infection prevention and control program at the Royal Prima Hospital was running well. Management support has been running optimally.